Common N-acetylgalactosamine-6-sulfate sulfatase (GALNS) exon mutations in Brazilian patients with mucopolysaccharidosis (MPS IVA) - Dieter, Tatiana (2007)
Morquio A Syndrome (mucopolysaccharidosis IVA - MPS IVA, OMIM# 253000) is an autosomal recessive inborn error of metabolism caused by the deficiency of N-acetylgalactosamine-6-sulfate sulfatase (GALNS). We investigated five unrelated Brazilian MPS IVA families for mutations in exons 4, 5, 9 and 10 of the GALNS gene. Six out of the 10 mutant alleles were identified. Taken together with a previous study, which included six unrelated families, common mutations among Brazilian patients were p.N164T, p.G116S and p.G301C. Among one hundred control subjects three novel silent mutations were found (p.A107A; GCC → GCT, p.Y108Y; TAC → TAT, p.P357P; CCG → CCA). Screening starting with exons 4, 5, 9, 10 and 11 may be a good strategy for genotyping of Brazilian patients since these exons include 73% of all mutations identified in the current and previous studies.